Prediction and Sensitivity Analysis of CO2 Capture by Amine Solvent Scrubbing Technique Based on BP Neural Network - Fu, Jiangtao; Chang, Yufeng; Huang, Bijie (Frontiers in Bioengineering and Biotechnology, 2022)
With the rapid development of artificial intelligence, bionic algorithm has been gradually applied in various fields, and neural network has become an important and hot issue in the field of scientific research and engineering in recent years. This paper proposes a BP Neural Network model to predict the capture ability and sensitivity of CO2 in MEA aqueous scrubbing technique from a 2*1000MW coal-fired power plant expansion project in eastern China. The predicted values agree well with experimental data with a satisfactory mean square root error (MSRE) ranging from 0.001945 to 0.002372 when the change of circulation amount of MEA, and the accuracy of prediction results of BPNN algorithm is as high as 96.6%. Sensitivity analysis results suggested that the flue gas amount has a marginal effect on the system performance, while further attention should be paid to the MEA circulation amount, which is crucial to the carbon dioxide capture amount. The temperature profiles show the typical behavior of the reactive absorption column where a temperature bulge can be seen at the bottom of the column due to the high L/G ratio of the experimental and prediction results. The coefficient of correlation R2 with the change of MEA circulation amount, change of CO2 concentration and steam consumption are 0.97722, 0.99801 and 0.98258 respectively. These results demonstrated that the present study has established the BPNN algorithm as a consistent, reliable and robust system identification tool for carbon dioxide capture by the amine solvent scrubbing technique of operation in coal-fired power plants.